2006
DOI: 10.1256/qj.05.55
|View full text |Cite
|
Sign up to set email alerts
|

Intense convective systems in West Africa and their relationship to the African easterly jet

Abstract: SUMMARYFor May-September 1998, convective systems in West Africa were identified from observations by the Tropical Rainfall Measuring Mission satellite Microwave Imager at 85 GHz. Using re-analysis data, the 10-day average position of the African easterly jet (AEJ) was diagnosed from the 700 hPa zonal winds. The distance from each convective system's centroid to the axis of the AEJ was calculated. Each convective system's minimum brightness temperatures were ranked so that intense convective systems were defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 50 publications
10
73
0
Order By: Relevance
“…They found that the forcing from the high terrain and shear associated with the AEJ would favour producing intense convective systems. Laing et al (2008Laing et al ( ) employed 5 years (1999Laing et al ( -2003 of digital infrared imagery for May to August and confirmed the results of Mohr and Thorncroft (2006).…”
Section: Background: the African Easterly Jet Of The Northern Hemispherementioning
confidence: 79%
See 2 more Smart Citations
“…They found that the forcing from the high terrain and shear associated with the AEJ would favour producing intense convective systems. Laing et al (2008Laing et al ( ) employed 5 years (1999Laing et al ( -2003 of digital infrared imagery for May to August and confirmed the results of Mohr and Thorncroft (2006).…”
Section: Background: the African Easterly Jet Of The Northern Hemispherementioning
confidence: 79%
“…They have also found a negative meridional potential vorticity (PV) gradient, which is consistent with theoretical expectations. Mohr and Thorncroft (2006) examined the relationship between intense convective systems and the AEJ during May to September 1998. They found that the forcing from the high terrain and shear associated with the AEJ would favour producing intense convective systems.…”
Section: Background: the African Easterly Jet Of The Northern Hemispherementioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with Guy et al (2011), AEW regimes produced an increased occurrence of larger systems in the ConNE, ConNW and coastal regions. Environmental factors such as strong lowlevel vertical wind shear aid the organization of intense convective systems (Frank, 1978;Rowell and Milford, 1993;Johnson et al, 2005;Mohr and Thorncroft, 2006;Nicholls and Mohr, 2010) over land. Stratiform precipitation is formed through the decay of convective regions and broad mesoscale ascent in the associated stratiform region (Zipser, 1969;Houze, 1977;Houze et al, 1989).…”
Section: Precipitation Feature Characteristicsmentioning
confidence: 99%
“…Surface westerly winds are overlaid by the AEJ, with potentially unstable conditions at low levels. This instability leads to the formation and maintenance of (often intense) MCSs (Aspliden et al, 1976;Payne and McGarry, 1977;Houze and Betts, 1981;Barnes and Sieckman, 1984;Rowell and Milford, 1993;Hodges and Thorncroft, 1997;Mohr and Thorncroft, 2006;Nicholls and Mohr, 2010). These westward-moving systems generally exhibit a linear (squall line) morphology over the continent (Hamilton et al, 1945;Eldridge, 1957;Bolton, 1984), a non-squall (amorphous) morphology over the eastern Atlantic Houze, 2003, 2006;Fuentes et al, 2008), and a transition stage upon exiting the coast (Sall and Sauvageot, 2005;DeLonge et al, 2010).…”
Section: Introductionmentioning
confidence: 99%